TB case detection in Tajikistan - analysis of existing obstacles - Alexei Korobitsyn; Oktam Bobokhojaev; Thomas Mohr; Jamila Ismoilova; Mavluda Makhmudova; Alex Trusov (University Library System, University of Pittsburgh, 2013)
Background: Tajikistan National TB Control Program Objective: (1) To identify the main obstacles to increasing TB Detection in Tajikistan. (2) To identify interventions that improve TB detection. Methods: Review of the available original research data, health normative base, health systems performance and national economic data, following WHO framework for detection of TB cases, which is based on three scenarios of why incident cases of TB may not be notified. Results: Data analysis revealed that some aspects of TB case detection are more problematic than others and that there are gaps in the knowledge of specific obstacles to TB case detection. The phenomenon of "initial default" in Tajikistan has been documented; however, it needs to be studied further. The laboratory services detect infectious TB cases effectively; however, referrals of appropriate suspects for TB diagnosis may lag behind. The knowledge about TB in the general population has improved. Yet, the problem of TB related stigma persists, thus being an obstacle for effective TB detection. High economic cost of health services driven by under-the-table payments was identified as another barrier for access to health services. Conclusion: Health system strengthening should become a primary intervention to improve case detection in Tajikistan. More research on reasons contributing to the failure to register TB cases, as well as factors underlying stigma is needed.